Anaerobic digestion of organic solid waste for energy production - Nayono, Satoto Endar (Karlsruher Berichte zur Ingenieurbiologie / Institut für Ingenieurbiologie und Biotechnologie des Abwassers, Universität Karlsruhe, 2010)
Anaerobic digestion of the organic fraction of municipal solid waste as such or together with food waste, press water or patatoes sludge was investigated to equilibrate methane production within a day or over the weekend, when no OFMSW was available. A stable co-digestion process could be achieved with COD degradation between 60 and 80 %. The max. organic loading rates were 28 kg COD/L,d. For stable methane production the OLR during Co-digestion should not excede 22,5 kg/L,d.